Antibacterial mildew-proof superfine fiber synthetic leather and preparation method thereof

By using composite fiber and needle punching technology to form the base fabric in the microfiber leather material, and combining hydrophilic treatment and antibacterial and antistatic liquid soaking technology, a microfiber synthetic leather with excellent antibacterial and antistatic properties is prepared, which solves the problem Existing materials are prone to bacterial growth and have poor antistatic properties.

CN119352308APending Publication Date: 2025-01-24FUJIAN ZHONGYU WATERBORNE MICROFIBER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475760.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing microfiber leather materials have a single function, are prone to bacterial growth, and have low antistatic properties, which cannot meet the medical needs of people who are increasingly paying attention to health care.

Method used

PET/PA6 composite hollow microfiber and PAN nanofiber are used for compounding. The base fabric is formed through processes such as acupuncture, heat treatment and roller rolling. It is then treated in a sodium hydroxide solution to improve hydrophilicity, and then immersed in antibacterial and antistatic properties. Two dipping and two rolling treatments are carried out in the liquid, combined with infrared pre-drying and hot air oven drying, to prepare antibacterial and mildew-proof microfiber synthetic leather.

Benefits of technology

It realizes the excellent antibacterial performance of ultra -fine fiber synthesis and the persistence of antichattering performance, while maintaining good mechanical properties, breathability and water absorption, and meets the needs of health materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096063730000111
    Figure BDA0005096063730000111
  • Figure BDA0005096063730000121
    Figure BDA0005096063730000121
Patent Text Reader

Abstract

The invention relates to the technical field of textile materials, in particular to antibacterial mildew-proof superfine fiber synthetic leather and a preparation method thereof. The preparation method of the antibacterial and mildew-proof superfine fiber synthetic leather comprises the following steps: S1, preparing and needling the composite superfine fiber bag; s2, subsequent needling and heat treatment; s3, carrying out hydrophilic treatment; s4, antibacterial and antistatic treatment, wherein the hydrophilic base cloth is soaked in antibacterial and antistatic liquid to be subjected to two-time soaking and two-time rolling treatment. And performing infrared pre-drying and hot air oven drying to obtain the antibacterial and mildew-proof superfine fiber synthetic leather. According to the novel preparation method of the antibacterial mildew-proof superfine fiber synthetic leather provided by the invention, the antibacterial and antistatic properties of the product are improved, good mechanical properties and comfort are kept, meanwhile, the feasibility of environmental protection and a production process is considered, and the novel preparation method has a very good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of textile materials, and in particular to an antibacterial and mildew-proof ultrafine fiber synthetic leather and a preparation method thereof. Background Art

[0002] Superfine fiber synthetic leather is developed on the basis of fully analyzing natural leather. Superfine fiber synthetic leather is made of bundled superfine fiber and polyurethane through special processing. It adopts nylon superfine fiber with similar structure and performance to bundled collagen fiber in natural leather, and is made into non-woven fabric with three-dimensional network structure, and then filled with polyurethane with open microporous structure with excellent performance through post-processing. Natural leather, also known as genuine leather, has pores, but sometimes it is difficult to see with the naked eye. Superfine fiber polyurethane synthetic leather base has excellent air permeability like genuine leather, and has better physical properties and more stable surface than genuine leather, which makes it almost replace genuine leather. It is widely used in clothing jackets, furniture sofas, decorative soft bags, gloves, car seats, car interiors, photo frames and albums, notebook covers, electronic product protective covers and daily necessities.

[0003] Bacteria have a great impact on human activities and are the pathogens of many diseases, including tuberculosis, gonorrhea, anthrax, syphilis, plague and other diseases are all caused by bacteria. However, the existing microfiber leather materials have single functions and are easy to breed bacteria, which is not good for health. For people who pay more and more attention to health care, it cannot meet the medical needs, and has low anti-static properties and poor usage experience. Summary of the invention

[0004] The purpose of this application is to provide an antibacterial and mildew-proof microfiber synthetic leather and a preparation method thereof in view of the shortcomings of the current technology. The antibacterial and mildew-proof microfiber synthetic leather of this application has excellent antibacterial properties, good and durable antistatic properties, and good mechanical properties, air permeability and water absorption properties.

[0005] In a first aspect, the present application provides a method for preparing antibacterial and mildew-proof microfiber synthetic leather, which adopts the following technical scheme: A method for preparing antibacterial and mildew-proof microfiber synthetic leather comprises the following steps: S1. Compounding PET / PA6 composite hollow ultrafine fibers and PAN nanofibers in a mass ratio of 4:1 to obtain a composite ultrafine fiber package, unpacking and loosening the composite ultrafine fiber package, combing it into a single-layer fiber web using a carding machine, and then passing it through a cross-lapping machine to form a composite layer fiber web; the composite layer fiber web is needle-punched at a frequency of 700-900 times / min by a needle-punching machine to obtain a pre-needle-punched non-woven fabric; S2: The pre-needled nonwoven fabric is subjected to bidirectional needle punching by a number of subsequent needle punching machines at a frequency of 1300-1500 times / min, forming a density of 0.48-0.55g / cm 3 The needle-punched nonwoven fabric is then heat-treated with hot air at 140°C and rolled at 80°C to form an apparent density of 0.59-0.66 g / cm 3 PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S3, placing the PAN-PET / PA6 ultrafine fiber synthetic leather base fabric into a 3% sodium hydroxide solution by mass, treating it in a water bath at 80-85° C. for 30-40 min, taking it out and washing it with pure water for 3 times, and then sending it into a dryer for pre-drying to obtain a hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S4. Immerse the hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric in antibacterial and antistatic liquid, perform double immersion and double rolling treatment, with a rolling rate of 70%, and then use infrared pre-drying to maintain the surface temperature of the ultrafine fiber synthetic leather base fabric at 60°C. After 10 minutes, transfer it to a 110°C hot air oven for drying for 30 minutes to obtain antibacterial and mildew-proof ultrafine fiber synthetic leather, wherein the polyurethane content of the antibacterial and mildew-proof ultrafine fiber synthetic leather is 30-35%; wherein the antibacterial and antistatic liquid, in terms of mass parts, comprises the following raw materials for preparation: 85-90 parts of aqueous polyurethane emulsion, 4-5 parts of composite antibacterial agent, 6-8 parts of antistatic agent, and 1.3-1.5 parts of dispersant.

[0006] By adopting the above technical scheme, the preparation method of the antibacterial and mildew-proof microfiber synthetic leather of the present application includes multiple steps, each of which has its specific role and synergistic effect, and finally obtains a synthetic leather with excellent antibacterial performance, good antistatic performance and durability. S1: Preparation and needling of composite microfiber package, PET / PA6 composite hollow microfiber and PAN nanofiber are compounded in a mass ratio of 4:1 to form a composite microfiber package. After opening the package and loosening, it is combed into a single-layer fiber web by a carding machine, and then formed into a composite layer fiber web by a cross-lapping machine. Use a needle punching machine for pre-needling to form a pre-needled non-woven fabric. PET / PA6 composite hollow microfiber provides good mechanical strength and durability, while PAN nanofiber increases mechanical properties, air permeability and water absorption. Through the needling process, the fibers are more tightly bonded, which improves the strength and stability of the non-woven fabric. S2: Subsequent needling and heat treatment, the pre-needled non-woven fabric is bidirectionally needled by multiple needling machines at a higher frequency to form a needle-punched non-woven fabric with a higher density. Hot air heat treatment and roller pressing further increase the density and apparent density of the non-woven fabric. High-density needle-punched non-woven fabric has better mechanical properties and structural stability. Heat treatment and roller pressing make the fibers more closely bonded, improving the durability and waterproof performance of the material. S3: Hydrophilic treatment, the base fabric is placed in a sodium hydroxide solution for treatment to improve its hydrophilicity. Washing and pre-drying to obtain a hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric. The hydrophilic treatment enables the base fabric to better absorb the antibacterial and antistatic liquid during subsequent antibacterial treatment, thereby improving the antibacterial effect. S4: Antibacterial and antistatic treatment, the hydrophilic base fabric is immersed in the antibacterial and antistatic liquid for two-immersion and two-rolling treatment. Infrared pre-drying and hot air oven drying to obtain antibacterial and mildew-proof ultrafine fiber synthetic leather. The components in the antibacterial and antistatic liquid work together to provide excellent antibacterial and antistatic properties. The role and synergy of each component in the antibacterial and antistatic liquid: The water-based polyurethane emulsion provides the matrix material, giving the synthetic leather basic physical properties. The composite antimicrobial agent provides antimicrobial properties and inhibits bacterial growth. The antistatic agent provides antistatic properties and reduces static electricity accumulation. The dispersant ensures that the components are evenly dispersed and improves the stability of the material properties. It promotes the effective combination of the components and improves the overall performance. In summary, the present application successfully prepares a microfiber synthetic leather with excellent antimicrobial properties, good antistatic properties and durability through precise control of multiple steps and the synergistic effect of the components.

[0007] Preferably, the mass ratio of PET to PA6 in the PET / PA6 composite hollow ultrafine fiber is 7:3.

[0008] Preferably, the solid content of the aqueous polyurethane emulsion is 40%.

[0009] Preferably, the composite antibacterial agent is prepared by mixing a modified silver-zinc-doped silica antibacterial agent and modified chitosan in a mass ratio of 1:2.

[0010] By adopting the above technical scheme, the composite antibacterial agent is one of the core components of the antibacterial and mildew-proof microfiber synthetic leather of the present application, and its main function is to give the synthetic leather excellent antibacterial properties. The modified silver-zinc-doped silica antibacterial agent can release active ions (such as silver ions and zinc ions), which can destroy the structure of bacterial cells and kill bacteria. The modified chitosan achieves high-efficiency antibacterial properties by changing the permeability of bacterial cell membranes and inhibiting the DNA transcription process inside microbial cells. The combination of the two can significantly improve the antibacterial and stability of microfiber synthetic leather, and it is long-lasting and efficient. Synergistic effect between modified silver-zinc-doped silica antibacterial agent and modified chitosan: There is a synergistic effect between the modified silver-zinc-doped silica antibacterial agent and the modified chitosan, and this synergistic effect is mainly reflected in the following aspects: Enhanced antibacterial properties: The modified silver-zinc-doped silica antibacterial agent can release more active ions, and the modified chitosan can improve the utilization rate of these active ions, thereby further enhancing the antibacterial properties. Improve stability: The modified silver-zinc-doped silica antibacterial agent has high thermal stability and chemical stability, while the modified chitosan can improve its dispersibility and compatibility in the polyurethane matrix, thereby improving the stability of the entire system. Extend service life: Since both the modified silver-zinc-doped silica antibacterial agent and the modified chitosan have good durability, their combined use can extend the service life of the microfiber synthetic leather. In summary, the composite antibacterial agent plays a key role in this application, not only improving the antibacterial properties of the microfiber synthetic leather, but also enhancing its stability and service life.

[0011] Preferably, the preparation method of the modified silver-zinc-doped silica antibacterial agent comprises the following steps: S51. At room temperature, add 100 mL of tetra-n-butyl silicate to 150 mL of ethanol and stir for 30 min to form solution A. S52, adding 1 g of silver nitrate and 6 g of zinc nitrate to a solution consisting of 100 mL of ethanol, 17 mL of acetic acid and 48 mL of water to form solution B; S53, adding solution B dropwise into solution A, stirring for 40 min, heating to 45° C., standing for aging for 12 h, then centrifuging, washing, drying at 95° C. for 12 h, and finally calcining at 530° C. for 3 h, cooling, and grinding to obtain silver-zinc-doped silica; S54, mixing 0.5 g of γ-(methacryloyloxy)propyltrimethoxysilane with 60 g of ethanol and 10 g of water, and hydrolyzing for 4 h to obtain a mixture C; S55. Add the obtained silver-zinc-doped silica to mixture C, then heat to 43°C, stir at 200 r / min for 250 min, and finally filter, wash, dry and grind at 85°C to obtain a modified silver-zinc-doped silica antibacterial agent with an average particle size of 20 nanometers.

[0012] By adopting the above technical scheme, the effects and synergistic effects of the prepared modified silver-zinc-doped silica antibacterial agent are mainly reflected in the following aspects: 1. Excellent antibacterial effect and long-term antibacterial ability: The modified silver-zinc-doped silica antibacterial agent can release active ions (such as silver ions and zinc ions), which can destroy the structure of bacterial cells and kill bacteria. In addition, due to its smaller particle size (20 nanometers), it can provide a larger specific surface area, increase the release of active ions such as silver and zinc, and thus enhance the antibacterial properties. 2. Improve the antibacterial property and stability of microfiber synthetic leather: There is a synergistic effect between modified chitosan and modified silver-zinc-doped silica antibacterial agent, which can significantly improve the antibacterial property and stability of microfiber synthetic leather, and it is long-lasting and efficient.

[0013] Preferably, the preparation method of the modified chitosan is: adding 20g of chitosan to 200ml of acetic acid solution with a mass concentration of 3%, stirring and dissolving to obtain a chitosan solution; adding 70g of tannic acid to 500ml of methanol, stirring and dissolving to obtain a tannic acid solution; adjusting the temperature of the chitosan solution to 36°C, adding the tannic acid solution and 6g of N-hydroxysuccinimide while stirring, stirring and reacting for 24h, and after the reaction is completed, dialyzing and freeze-drying to obtain the modified chitosan.

[0014] By adopting the above technical scheme, chitosan itself has excellent antibacterial properties, and high-efficiency antibacterial properties are achieved by changing the permeability of bacterial cell membranes and inhibiting the DNA transcription process inside microbial cells. After being modified with tannic acid, the antibacterial properties of chitosan are improved to a certain extent. This is because the catechol group in tannic acid can form a strong hydrogen bond with polyurethane, improve the compatibility of modified chitosan with the matrix, and thus enhance the antibacterial properties of ultrafine fiber synthetic leather. There is a synergistic effect between modified chitosan and modified silver-zinc-doped silica antibacterial agent, which can significantly improve the antibacterial and stability of ultrafine fiber synthetic leather, making it have long-lasting and efficient antibacterial ability. The modified chitosan can better combine with substrates such as polyurethane to improve the overall performance of the composite material. This helps to improve the mechanical properties, air permeability and water absorption of ultrafine fiber synthetic leather. The presence of modified chitosan may help other functional components (such as modified carbon nanotubes) to be evenly dispersed in the material, further improving the performance of the material. In summary, the modified chitosan in this application not only improves the antibacterial performance, but also enhances the stability and interface compatibility of the material, and synergizes with other functional components to jointly improve the comprehensive performance of the antibacterial and mildew-proof microfiber synthetic leather.

[0015] Preferably, the antistatic agent is composed of modified carbon nanotubes and behenyltrimethylammonium chloride in a mass ratio of 5:3.

[0016] By adopting the above technical scheme, the modified carbon nanotubes are grafted with organic molecular chains through chemical bonding to form an organic layer on its surface, which can greatly improve the interfacial compatibility between carbon nanotubes and polyurethane, reduce the agglomeration of carbon nanotubes, and promote the uniform dispersion of modified carbon nanotubes in polyurethane. In this way, the modified carbon nanotubes can give full play to their antistatic properties and enhance the polyurethane. In addition, the grafting of organic molecular chains on carbon nanotubes can effectively prevent the migration and exudation of organic molecules, ensuring the durability of various properties. Behenyltrimethylammonium chloride is a quaternary ammonium salt compound with a positive charge. When it comes into contact with negatively charged bacteria, it will produce a strong electrostatic interaction and produce a strong adsorption effect on the bacteria. This adsorption effectively improves the antibacterial and antistatic properties of ultrafine fiber synthetic leather. Synergistic effect between modified carbon nanotubes and behenyltrimethylammonium chloride: modified carbon nanotubes and behenyltrimethylammonium chloride work together in antibacterial and mildew-proof ultrafine fiber synthetic leather, forming a synergistic effect. The modified carbon nanotubes provide good antistatic properties, while the behenyl trimethyl ammonium chloride enhances the antibacterial properties. The two complement each other, making the microfiber synthetic leather have both good antistatic properties and excellent antibacterial properties. At the same time, due to the strong interaction between the modified carbon nanotubes and behenyl trimethyl ammonium chloride, they are not easy to fall off during the rinsing process, thereby improving the performance durability of the product.

[0017] Preferably, the method for preparing the modified carbon nanotubes comprises the following steps: S81, 40g of carbon nanotubes were placed in a conical flask, and then 1.5L of 98% concentrated sulfuric acid and 0.5L of 98% concentrated hydrochloric acid were added, and ultrasonic treatment was performed in a 65°C water bath for 10h. After the mixture was cooled to room temperature, deionized water was added to dilute it, centrifuged, and washed with anhydrous ethanol and deionized water for 5 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes; S82, 25.2g of diethylenetriamine, 100g of methoxypolyethylene glycol aldehyde, 30mL of piperidine and 200mL of pyridine were stirred and mixed in a reactor equipped with a stirring device, and the temperature was raised to 42°C, and the reaction was kept warm for 10h. After the reaction was completed, it was naturally cooled, the solvent was removed by rotary evaporation, and then purified by column chromatography and rotary evaporation to obtain intermediate 1; S83. In a reactor equipped with a stirring device, 20 g of carboxylated carbon nanotubes were mixed with 200 mL of N,N-dimethylformamide, and magnetically stirred for 3 h to uniformly disperse the carboxylated carbon nanotubes. Then, 40 g of intermediate 1, 2.5 g of dicyclohexylcarbodiimide and 0.7 g of 4-dimethylaminopyridine were added in sequence. After uniform stirring, the mixture was placed in a 43°C water bath for 5 h of ultrasonic treatment. The water bath was then removed and magnetically stirred for 12 h at room temperature. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol 4 times, dried and ground to obtain intermediate 2. S84. Under nitrogen protection, mix 20 g of intermediate 2 with 200 mL of N,N-dimethylformamide in a reactor equipped with a stirring device. After magnetic stirring for 70 min, add 30 g of 6-chloro-1-hexanol and 15 g of potassium carbonate. Control the reaction temperature to 78 ° C. Stir the reaction for 14 h. After the reaction is completed, filter, wash with anhydrous ethanol three times, dry, and grind to obtain modified carbon nanotubes.

[0018] By adopting the above technical solution, the prepared modified carbon nanotubes are grafted with organic molecular chains through chemical bonding, that is, an organic layer is formed on the surface of the carbon nanotubes, which can greatly improve the interface compatibility between the carbon nanotubes and polyurethane, reduce the agglomeration of the carbon nanotubes, thereby promoting the uniform dispersion of the modified carbon nanotubes in the polyurethane, giving full play to the antistatic properties of the carbon nanotubes, and also enhancing the polyurethane; not only that, the carbon nanotubes grafted with organic molecular chains can effectively prevent the migration and seepage of organic molecules, and ensure the durability of various properties; in addition, the organic molecular chains contain Hydroxyl groups, polyethylene glycol, and quaternary ammonium salts form chemical bonds with the polyurethane molecular chains, increasing the interaction with the matrix, making the organic molecular chains less likely to fall off during rinsing and improving the durability of the performance; the introduction of the hydrophilic chain polyethylene glycol structure can greatly improve the hydrophilicity of the matrix, and the polyethylene glycol is a flexible chain segment that can further improve the mechanical properties of the matrix; the introduction of quaternary ammonium salt ions will produce strong electrostatic interactions between the positively charged and negatively charged bacteria, and will have a strong adsorption effect on the bacteria, effectively improving the antibacterial and antistatic properties of the microfiber synthetic leather.

[0019] Preferably, the dispersant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1:1.

[0020] By adopting the above technical scheme, firstly, the main function of the dispersant is to promote the uniform dispersion of the components in the antibacterial and antistatic liquid in the aqueous polyurethane emulsion, prevent the particles from agglomerating, and improve the stability of the system. Octadecyl trimethyl ammonium bromide is a cationic surfactant with good emulsification, dispersing and wetting properties, which can effectively reduce the surface tension of the liquid and make the oily components better dispersed in water. Polyoxyethylene (10) tridecyl ether is a nonionic surfactant, which also has excellent emulsification, dispersing and wetting properties, and has good compatibility with a variety of substances. Secondly, the synergistic effect between octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether can further enhance the dispersion effect. The combined use of cationic surfactants and nonionic surfactants can form composite micelles, provide a larger specific surface area, and thus more effectively adsorb and stabilize various particles. This synergistic effect not only improves the dispersibility of the components in the antibacterial and antistatic liquid, but also helps to improve the antibacterial and antistatic properties of the final product. In summary, the dispersant is designed to be composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1:1. Through its good emulsifying, dispersing and wetting properties and the synergistic effect between the two, it ensures the uniform dispersion of the components in the antibacterial and antistatic liquid, improves the antibacterial and antistatic properties of the microfiber synthetic leather, and ensures the stability and durability of the product.

[0021] In a second aspect, the present application provides an antibacterial and mildew-proof microfiber synthetic leather, which adopts the following technical solution: As a general technical concept, the present application also provides antibacterial and mildew-proof microfiber synthetic leather produced by the above-mentioned method for preparing antibacterial and mildew-proof microfiber synthetic leather.

[0022] In summary, the beneficial technical effects of this application are: 1. Excellent antibacterial properties: By using modified chitosan and modified silver-zinc-doped silica antibacterial agent, these two materials have a synergistic effect in antibacterial properties, which can significantly improve the antibacterial properties and stability of microfiber synthetic leather. Modified chitosan can change the permeability of bacterial cell membranes and inhibit the DNA transcription process inside microbial cells, while modified silver-zinc-doped silica antibacterial agent can release active ions to destroy bacterial cell structures, thereby killing bacteria.

[0023] 2. Good and durable antistatic performance: By introducing the prepared modified carbon nanotubes, the organic layer formed on its surface improves the interface compatibility with polyurethane, reduces the agglomeration phenomenon, and promotes uniform dispersion. This not only exerts the antistatic performance of carbon nanotubes, but also enhances the polyurethane. At the same time, the grafted organic molecular chain contains hydroxyl, polyethylene glycol, quaternary ammonium salt, etc., which produce chemical bonding with the polyurethane molecular chain, improve the interaction force, and ensure the durability of the performance.

[0024] 3. Good mechanical properties, air permeability and water absorption: After the needle punching and heat treatment process, the synthetic leather base fabric forms a structure with appropriate density and apparent density, ensuring the mechanical strength and durability of the material. At the same time, after the hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric is treated, the hydrophilicity of the matrix is ​​improved, which is beneficial to improve the air permeability and water absorption of synthetic leather.

[0025] 4. Environmentally friendly: The water-based polyurethane emulsion and other additives used in the antibacterial and antistatic liquid are environmentally friendly materials, reducing pollution to the environment.

[0026] 5. The process is simple and feasible: the entire preparation process uses existing industrial equipment and technology, which is easy to achieve large-scale production. DETAILED DESCRIPTION

[0027] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] In the following examples and preparation examples, 1 part means 100 g.

[0029] Preparation Example 1 Preparation of modified silver-zinc-doped silica antibacterial agent The preparation method of modified silver-zinc-doped silica antibacterial agent comprises the following steps: S51. At room temperature, add 100 mL of tetra-n-butyl silicate to 150 mL of ethanol and stir for 30 min to form solution A. S52, adding 1 g of silver nitrate and 6 g of zinc nitrate to a solution consisting of 100 mL of ethanol, 17 mL of acetic acid and 48 mL of water to form solution B; S53, adding solution B dropwise into solution A, stirring for 40 min, heating to 45° C., standing for aging for 12 h, then centrifuging, washing, drying at 95° C. for 12 h, and finally calcining at 530° C. for 3 h, cooling, and grinding to obtain silver-zinc-doped silica; S54, mixing 0.5 g of γ-(methacryloyloxy)propyltrimethoxysilane with 60 g of ethanol and 10 g of water, and hydrolyzing for 4 h to obtain a mixture C; S55. Add the obtained silver-zinc-doped silica to mixture C, then heat to 43°C, stir at 200 r / min for 250 min, and finally filter, wash, dry and grind at 85°C to obtain a modified silver-zinc-doped silica antibacterial agent with an average particle size of 20 nanometers.

[0030] Preparation Example 2 Preparation of modified chitosan The preparation method of modified chitosan is as follows: adding 20g of chitosan to 200ml of acetic acid solution with a mass concentration of 3%, stirring and dissolving to obtain a chitosan solution; adding 70g of tannic acid to 500ml of methanol, stirring and dissolving to obtain a tannic acid solution; adjusting the temperature of the chitosan solution to 36°C, adding the tannic acid solution and 6g of N-hydroxysuccinimide while stirring, stirring and reacting for 24h, and after the reaction is completed, dialyzing and freeze-drying to obtain the modified chitosan.

[0031] Preparation Example 3 Preparation of modified carbon nanotubes The method for preparing modified carbon nanotubes comprises the following steps: S81, 40g of carbon nanotubes were placed in a conical flask, and then 1.5L of 98% concentrated sulfuric acid and 0.5L of 98% concentrated hydrochloric acid were added, and ultrasonic treatment was performed in a 65°C water bath for 10h. After the mixture was cooled to room temperature, deionized water was added to dilute it, centrifuged, and washed with anhydrous ethanol and deionized water for 5 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes; S82, 25.2g of diethylenetriamine, 100g of methoxypolyethylene glycol aldehyde, 30mL of piperidine and 200mL of pyridine were stirred and mixed in a reactor equipped with a stirring device, and the temperature was raised to 42°C, and the reaction was kept warm for 10h. After the reaction was completed, it was naturally cooled, the solvent was removed by rotary evaporation, and then purified by column chromatography and rotary evaporation to obtain intermediate 1; S83. In a reactor equipped with a stirring device, 20 g of carboxylated carbon nanotubes were mixed with 200 mL of N,N-dimethylformamide, and magnetically stirred for 3 h to uniformly disperse the carboxylated carbon nanotubes. Then, 40 g of intermediate 1, 2.5 g of dicyclohexylcarbodiimide and 0.7 g of 4-dimethylaminopyridine were added in sequence. After uniform stirring, the mixture was placed in a 43°C water bath for 5 h of ultrasonic treatment. The water bath was then removed and magnetically stirred for 12 h at room temperature. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol 4 times, dried and ground to obtain intermediate 2. S84. Under nitrogen protection, mix 20 g of intermediate 2 with 200 mL of N,N-dimethylformamide in a reactor equipped with a stirring device. After magnetic stirring for 70 min, add 30 g of 6-chloro-1-hexanol and 15 g of potassium carbonate. Control the reaction temperature to 78 ° C. Stir the reaction for 14 h. After the reaction is completed, filter, wash with anhydrous ethanol three times, dry, and grind to obtain modified carbon nanotubes.

[0032] Example 1 A method for preparing antibacterial and mildew-proof microfiber synthetic leather comprises the following steps: S1. Compounding PET / PA6 composite hollow ultrafine fibers and PAN nanofibers in a mass ratio of 4:1 to obtain a composite ultrafine fiber package, unpacking and loosening the composite ultrafine fiber package, carding it into a single-layer fiber web using a carding machine, and then forming a composite layer fiber web through a cross-lapping machine; the composite layer fiber web is needle-punched at a frequency of 700 times / min by a needle-punching machine to obtain a pre-needle-punched non-woven fabric; the mass ratio of PET to PA6 in the PET / PA6 composite hollow ultrafine fibers is 7:3; S2, the pre-needled nonwoven fabric is subjected to bidirectional needle punching at a frequency of 1300 times / min on a subsequent needle punching machine, forming a density of 0.48g / cm 3 The needle-punched nonwoven fabric is then heat-treated with hot air at 140°C and rolled at 80°C to form an apparent density of 0.59 g / cm 3 PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S3, placing the PAN-PET / PA6 ultrafine fiber synthetic leather base fabric into a 3% sodium hydroxide solution by mass, treating it in a water bath at 80° C. for 40 min, taking it out and washing it with pure water for 3 times, and then sending it into a dryer for pre-drying to obtain a hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S4, immerse the hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric in an antibacterial and antistatic liquid, perform double immersion and double rolling treatment, the rolling rate is 70%, and then use infrared pre-drying to maintain the surface temperature of the ultrafine fiber synthetic leather base fabric at 60°C, and after 10 minutes, transfer it to a 110°C hot air oven for drying for 30 minutes to obtain an antibacterial and mildew-proof ultrafine fiber synthetic leather, wherein the polyurethane content of the antibacterial and mildew-proof ultrafine fiber synthetic leather is 30%; wherein the antibacterial and antistatic liquid, by weight, is prepared from raw materials including: 85 parts of aqueous polyurethane emulsion (solid content is 40%) , 4 parts of composite antibacterial agent, 6 parts of antistatic agent, and 1.3 parts of dispersant, wherein the composite antibacterial agent is prepared by mixing modified silver-zinc-doped silica antibacterial agent and modified chitosan in a mass ratio of 1:2, the antistatic agent is composed of modified carbon nanotubes and docosyltrimethylammonium chloride in a mass ratio of 5:3, and the dispersant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1:1. The preparation method of the antibacterial and antistatic liquid is to stir and mix the components in the formula according to the mass ratio to obtain the antibacterial and antistatic liquid.

[0033] Example 2 A method for preparing antibacterial and mildew-proof microfiber synthetic leather comprises the following steps: S1. Compounding PET / PA6 composite hollow ultrafine fibers and PAN nanofibers in a mass ratio of 4:1 to obtain a composite ultrafine fiber package, unpacking and loosening the composite ultrafine fiber package, carding it into a single-layer fiber web using a carding machine, and then forming a composite layer fiber web through a cross-lapping machine; the composite layer fiber web is needle-punched at a frequency of 900 times / min by a needle-punching machine to obtain a pre-needle-punched non-woven fabric; the mass ratio of PET to PA6 in the PET / PA6 composite hollow ultrafine fibers is 7:3; S2, the pre-needled nonwoven fabric is subjected to bidirectional needle punching at a frequency of 1500 times / min on a subsequent needle punching machine, forming a density of 0.55g / cm 3 The needle-punched nonwoven fabric is then heat-treated with hot air at 140°C and rolled at 80°C to form an apparent density of 0.66 g / cm 3 PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S3, placing the PAN-PET / PA6 ultrafine fiber synthetic leather base fabric into a 3% sodium hydroxide solution by mass, treating it in a water bath at 85° C. for 30 min, taking it out and washing it with pure water for 3 times, and then sending it into a dryer for pre-drying to obtain a hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S4, immerse the hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric in an antibacterial and antistatic liquid, perform double immersion and double rolling treatment, the rolling rate is 70%, and then use infrared pre-drying to maintain the surface temperature of the ultrafine fiber synthetic leather base fabric at 60°C, and after 10 minutes, transfer it to a 110°C hot air oven for drying for 30 minutes to obtain an antibacterial and mildew-proof ultrafine fiber synthetic leather, wherein the polyurethane content of the antibacterial and mildew-proof ultrafine fiber synthetic leather is 35%; wherein the antibacterial and antistatic liquid, according to the mass percentage, is prepared from the following raw materials: 90 parts of aqueous polyurethane emulsion (solid content is 40%) , 5 parts of composite antibacterial agent, 8 parts of antistatic agent, and 1.5 parts of dispersant, wherein the composite antibacterial agent is prepared by mixing modified silver-zinc-doped silica antibacterial agent and modified chitosan in a mass ratio of 1:2, the antistatic agent is composed of modified carbon nanotubes and docosyltrimethylammonium chloride in a mass ratio of 5:3, and the dispersant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1:1. The preparation method of the antibacterial and antistatic liquid is to stir and mix the components in the formula evenly according to the mass ratio to obtain the antibacterial and antistatic liquid.

[0034] Example 3 A method for preparing antibacterial and mildew-proof microfiber synthetic leather comprises the following steps: S1. Compounding PET / PA6 composite hollow ultrafine fibers and PAN nanofibers in a mass ratio of 4:1 to obtain a composite ultrafine fiber package, unpacking and loosening the composite ultrafine fiber package, combing it into a single-layer fiber web using a carding machine, and then passing it through a cross-lapping machine to form a composite layer fiber web; the composite layer fiber web is needle-punched at a frequency of 800 times / min by a needle-punching machine to obtain a pre-needle-punched non-woven fabric; the mass ratio of PET to PA6 in the PET / PA6 composite hollow ultrafine fibers is 7:3; S2, the pre-needled nonwoven fabric is subjected to bidirectional needle punching at a frequency of 1400 times / min on a subsequent needle punching machine, forming a density of 0.51g / cm 3 The needle-punched nonwoven fabric is then heat-treated with hot air at 140°C and rolled at 80°C to form an apparent density of 0.61 g / cm 3 PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S3, placing the PAN-PET / PA6 ultrafine fiber synthetic leather base fabric into a 3% sodium hydroxide solution by mass, treating it in a water bath at 83° C. for 35 min, taking it out and washing it with pure water for 3 times, and then sending it into a dryer for pre-drying to obtain a hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S4, immersing the hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric in an antibacterial and antistatic liquid, performing a double immersion and double rolling treatment, with a rolling rate of 70%, and then using infrared pre-drying to maintain the surface temperature of the ultrafine fiber synthetic leather base fabric at 60°C, and after 10 minutes, transferring it to a 110°C hot air oven for drying for 30 minutes to obtain an antibacterial and mildew-proof ultrafine fiber synthetic leather, wherein the polyurethane content of the antibacterial and mildew-proof ultrafine fiber synthetic leather is 33%; wherein the antibacterial and antistatic liquid, in terms of mass fractions, comprises: 88 parts of aqueous polyurethane emulsion (solid content is 40%), 4.5 parts of a composite antibacterial agent, 7 parts of an antistatic agent, and 1.4 parts of a dispersant. The composite antibacterial agent is prepared by mixing a modified silver-zinc-doped silica antibacterial agent and a modified chitosan in a mass ratio of 1:2. The antistatic agent is composed of modified carbon nanotubes and docosyltrimethylammonium chloride in a mass ratio of 5:3. The dispersant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1:1. The preparation method of the antibacterial and antistatic liquid is as follows: after stirring and mixing the components in the formula evenly according to the mass ratio, the antibacterial and antistatic liquid is obtained.

[0035] Comparative Example 1 The same as Example 3, except that an equal amount of carbon nanotubes are used instead of modified carbon nanotubes.

[0036] Comparative Example 2 The same as Example 3, except that the composite antibacterial agent is a modified silver-zinc-doped silica antibacterial agent.

[0037] Comparative Example 3 The same as Example 3, except that the composite antibacterial agent is modified chitosan.

[0038] Comparative Example 4 The same as Example 3, except that the antistatic agent is modified carbon nanotubes.

[0039] Comparative Example 5 The same as Example 3, except that the antistatic agent is behenyltrimethylammonium chloride.

[0040] Comparative Example 6 The same as Example 3, except that the dispersant is octadecyltrimethylammonium bromide.

[0041] Comparative Example 7 The same as Example 3, except that the dispersant is polyoxyethylene (10) tridecyl ether.

[0042] Performance Testing 1. The antibacterial and mildew-proof microfiber synthetic leathers prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were sampled and tested as follows. The test results are shown in Table 1.

[0043] Mechanical properties test: According to GB / T 24218.3-2010 "Test methods for textile nonwovens Part 3: Determination of breaking strength and breaking elongation (strip method)", the breaking strength and breaking elongation of the leather base fabric were tested using a universal strength tester. The sample width was 50mm, the tensile speed was 100mm / min, and the gauge was 200mm; Moisture absorption performance test: According to GB / T4689.21-2008 "Determination of static water absorption of leather physical and mechanical tests", the static water absorption test of the leather base fabric is carried out at a test temperature of (20+2)℃; Air permeability test: According to GB / T24218.15-2018 "Textile nonwoven fabric test methods Part 15: Determination of air permeability", the air permeability of the sample is measured using a fully automatic air permeability tester. The test pressure is 100Pa and the test area is 20cm 2 ; Antistatic performance test: Place the sample at a temperature of 23°C and a relative humidity of 52% for 24 hours. The surface resistivity test refers to the test method in Appendix B of GB / T24249-2009, unit: Ω·m; Anti-mildew: tested in accordance with FZ / T60030-2009, the test object is Aspergillus niger ATCC16404; Antibacterial test: The test was carried out in accordance with GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", and the test object was Escherichia coli.

[0044] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The antibacterial and mildew-proof microfiber synthetic leathers prepared in Examples 1 to 3 have excellent antibacterial properties, good and durable antistatic properties, and good mechanical properties, air permeability and water absorption properties.

[0045] 2) The comparative analysis of the performance of the antibacterial and mildew-proof microfiber synthetic leather obtained in combination with Example 3 and Comparative Example 1 shows that the modified carbon nanotubes prepared in the present application are grafted with organic molecular chains through chemical bonding, that is, an organic layer is formed on the surface thereof, which can greatly improve the interfacial compatibility between the carbon nanotubes and polyurethane, reduce the agglomeration of the carbon nanotubes, thereby promoting the uniform dispersion of the modified carbon nanotubes in the polyurethane, giving full play to the antistatic properties of the carbon nanotubes, and also enhancing the polyurethane; moreover, the carbon nanotubes grafted with organic molecular chains can effectively prevent the migration and seepage of organic molecules, ensuring the maintenance of various properties. In addition, the organic molecular chain contains hydroxyl, polyethylene glycol, and quaternary ammonium salt, which produce chemical bonds with the polyurethane molecular chain, thereby improving the interaction force with the matrix, making the organic molecular chain less likely to fall off during rinsing, and improving the durability of the performance; the introduction of the hydrophilic chain polyethylene glycol structure can greatly improve the hydrophilicity of the matrix, and the polyethylene glycol is a flexible chain segment that can further improve the mechanical properties of the matrix; the introduction of quaternary ammonium salt ions will produce strong electrostatic interactions between the positively charged and negatively charged bacteria, and will have a strong adsorption effect on the bacteria, effectively improving the antibacterial and antistatic properties of the ultrafine fiber synthetic leather.

[0046] 3) The performance comparison analysis of the antibacterial and mildew-proof microfiber synthetic leather prepared in combination with Example 3 and Comparative Examples 2-3 shows that the composite antibacterial agent is prepared by mixing the modified silver-zinc-doped silica antibacterial agent and the modified chitosan in a mass ratio of 1:2. The synergistic effect between the modified silver-zinc-doped silica antibacterial agent and the modified chitosan is mainly reflected in the following aspects: Enhanced antibacterial performance: The modified silver-zinc-doped silica antibacterial agent can release more active ions, while the modified chitosan can improve the utilization rate of these active ions, thereby further enhancing the antibacterial performance. Improved stability: The modified silver-zinc-doped silica antibacterial agent has high thermal stability and chemical stability, while the modified chitosan can improve its dispersibility and compatibility in the polyurethane matrix, thereby improving the stability of the entire system. Extended service life: Since both the modified silver-zinc-doped silica antibacterial agent and the modified chitosan have good durability, their combined use can extend the service life of the microfiber synthetic leather.

[0047] 4) The performance comparison analysis of the antibacterial and mildew-proof ultrafine fiber synthetic leather obtained in combination with Example 3 and Comparative Examples 4-5 shows that the antistatic agent is composed of modified carbon nanotubes and docosyl trimethyl ammonium chloride in a mass ratio of 5:3, and the modified carbon nanotubes and docosyl trimethyl ammonium chloride are used together in the antibacterial and mildew-proof ultrafine fiber synthetic leather to form a synergistic effect. The modified carbon nanotubes provide good antistatic properties, while docosyl trimethyl ammonium chloride enhances the antibacterial properties. The two complement each other, so that the ultrafine fiber synthetic leather has both good antistatic properties and excellent antibacterial properties. At the same time, due to the strong interaction between the modified carbon nanotubes and docosyl trimethyl ammonium chloride, they are not easy to fall off during the rinsing process, thereby improving the performance durability of the product.

[0048] 5) The performance comparison analysis of the antibacterial and mildew-proof microfiber synthetic leather prepared in combination with Example 3 and Comparative Examples 6-7 shows that the dispersant is composed of octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1: 1. By utilizing the synergistic effect between them, through their good emulsification, dispersing and wetting properties and the synergistic effect between the two, the uniform dispersion of the components in the antibacterial and antistatic liquid is ensured, the antibacterial and antistatic properties of the microfiber synthetic leather are improved, and the stability and durability of the product are guaranteed.

[0049] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing antibacterial and mildew-proof microfiber synthetic leather, characterized in that: The following steps are involved: S1. Compounding PET / PA6 composite hollow ultrafine fibers and PAN nanofibers in a mass ratio of 4:1 to obtain a composite ultrafine fiber package, unpacking and loosening the composite ultrafine fiber package, combing it into a single-layer fiber web using a carding machine, and then passing it through a cross-lapping machine to form a composite layer fiber web; the composite layer fiber web is needle-punched at a frequency of 700-900 times / min by a needle-punching machine to obtain a pre-needle-punched non-woven fabric; S2: The pre-needled nonwoven fabric is subjected to bidirectional needle punching by a number of subsequent needle punching machines at a frequency of 1300-1500 times / min, forming a density of 0.48-0.55g / cm 3 The needle-punched nonwoven fabric is then heat-treated with hot air at 140°C and rolled at 80°C to form an apparent density of 0.59-0.66 g / cm 3 PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S3, placing the PAN-PET / PA6 ultrafine fiber synthetic leather base fabric into a sodium hydroxide solution with a mass fraction of 3%, treating it in a water bath at 80-85°C for 30-40 minutes, taking it out and washing it with pure water for 3 times, and then sending it into a dryer for pre-drying to obtain a hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric; S4. Immerse the hydrophilic PAN-PET / PA6 ultrafine fiber synthetic leather base fabric in antibacterial and antistatic liquid, perform double immersion and double rolling treatment, with a rolling rate of 70%, and then use infrared pre-drying to maintain the surface temperature of the ultrafine fiber synthetic leather base fabric at 60°C. After 10 minutes, transfer it to a 110°C hot air oven for drying for 30 minutes to obtain antibacterial and mildew-proof ultrafine fiber synthetic leather, wherein the polyurethane content of the antibacterial and mildew-proof ultrafine fiber synthetic leather is 30-35%; wherein the antibacterial and antistatic liquid, in terms of mass parts, comprises the following raw materials for preparation: 85-90 parts of aqueous polyurethane emulsion, 4-5 parts of composite antibacterial agent, 6-8 parts of antistatic agent, and 1.3-1.5 parts of dispersant.

2. The method for preparing the antibacterial and mildew-proof microfiber synthetic leather according to claim 1, characterized in that: The mass ratio of PET to PA6 in the PET / PA6 composite hollow ultrafine fiber is 7:

3.

3. The method for preparing the antibacterial and mildew-proof microfiber synthetic leather according to claim 1, characterized in that: The solid content of the aqueous polyurethane emulsion is 40%.

4. The method for preparing antibacterial and mildew-proof microfiber synthetic leather according to claim 1, characterized in that: The composite antibacterial agent is prepared by mixing a modified silver-zinc-doped silicon dioxide antibacterial agent and modified chitosan in a mass ratio of 1:

2.

5. The method for preparing antibacterial and mildew-proof microfiber synthetic leather according to claim 4, characterized in that: The preparation method of the modified silver-zinc-doped silica antibacterial agent comprises the following steps: S51. At room temperature, add 100 mL of tetra-n-butyl silicate to 150 mL of ethanol and stir for 30 min to form solution A. S52, adding 1 g of silver nitrate and 6 g of zinc nitrate to a solution consisting of 100 mL of ethanol, 17 mL of acetic acid and 48 mL of water to form solution B; S53, adding solution B dropwise into solution A, stirring for 40 min, heating to 45° C., standing for aging for 12 h, then centrifuging, washing, drying at 95° C. for 12 h, and finally calcining at 530° C. for 3 h, cooling, and grinding to obtain silver-zinc-doped silica; S54, mixing 0.5 g of γ-(methacryloyloxy)propyltrimethoxysilane with 60 g of ethanol and 10 g of water, and hydrolyzing for 4 h to obtain a mixture C; S55. Add the obtained silver-zinc-doped silica to mixture C, then heat to 43°C, stir at 200 r / min for 250 min, and finally filter, wash, dry and grind at 85°C to obtain a modified silver-zinc-doped silica antibacterial agent with an average particle size of 20 nanometers.

6. The method for preparing antibacterial and mildew-proof microfiber synthetic leather according to claim 4, characterized in that: The preparation method of the modified chitosan is as follows: adding 20g of chitosan to 200ml of acetic acid solution with a mass concentration of 3%, stirring and dissolving to obtain a chitosan solution; adding 70g of tannic acid to 500ml of methanol, stirring and dissolving to obtain a tannic acid solution; adjusting the temperature of the chitosan solution to 36°C, adding the tannic acid solution and 6g of N-hydroxysuccinimide while stirring, stirring and reacting for 24h, and after the reaction is completed, dialyzing and freeze-drying to obtain the modified chitosan.

7. The method for preparing antibacterial and mildew-proof microfiber synthetic leather according to claim 1, characterized in that: The antistatic agent is composed of modified carbon nanotubes and docosyltrimethylammonium chloride in a mass ratio of 5:

3.

8. The method for preparing antibacterial and mildew-proof microfiber synthetic leather according to claim 7, characterized in that: The method for preparing the modified carbon nanotubes comprises the following steps: S81, placing 40 g of carbon nanotubes in a conical flask, then adding 1.5 L of 98% concentrated sulfuric acid and 0.5 L of 98% concentrated hydrochloric acid, and ultrasonically treating in a 65°C water bath for 10 h, adding deionized water to dilute the mixture after cooling to room temperature, centrifuging, and washing with anhydrous ethanol and deionized water for 5 times in sequence, drying, and grinding to obtain carboxylated carbon nanotubes; S82, in a reactor equipped with a stirring device, 25.2 g of diethylenetriamine, 100 g of methoxypolyethylene glycol aldehyde, 30 mL of piperidine and 200 mL of pyridine were stirred and mixed uniformly, the temperature was raised to 42° C., and the reaction was kept warm for 10 hours. After the reaction was completed, the reaction was naturally cooled, the solvent was removed by rotary evaporation, and then purified by column chromatography and rotary evaporation to obtain intermediate 1; S83. In a reactor equipped with a stirring device, 20 g of carboxylated carbon nanotubes were mixed with 200 mL of N,N-dimethylformamide, and magnetically stirred for 3 h to uniformly disperse the carboxylated carbon nanotubes. Then, 40 g of intermediate 1, 2.5 g of dicyclohexylcarbodiimide and 0.7 g of 4-dimethylaminopyridine were added in sequence. After uniform stirring, the mixture was placed in a 43°C water bath for 5 h of ultrasonic treatment. The water bath was then removed and magnetically stirred for 12 h at room temperature. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol 4 times, dried and ground to obtain intermediate 2. S84. Under nitrogen protection, mix 20 g of intermediate 2 with 200 mL of N,N-dimethylformamide in a reactor equipped with a stirring device. After magnetic stirring for 70 min, add 30 g of 6-chloro-1-hexanol and 15 g of potassium carbonate. Control the reaction temperature to 78 ° C. Stir the reaction for 14 h. After the reaction is completed, filter, wash with anhydrous ethanol three times, dry, and grind to obtain modified carbon nanotubes.

9. The method for preparing antibacterial and mildew-proof microfiber synthetic leather according to claim 1, characterized in that: The dispersant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 1:

1. 10.An antibacterial and mildew-proof microfiber synthetic leather, characterized in that: The antibacterial and mildew-proof ultrafine fiber synthetic leather is prepared by the preparation method of any one of claims 1 to 9.